Adipose-Derived Stem Cell: “Treat or Trick” - Siti Syahira Airuddin (MDPI AG, 2021)
Stem cells have been widely used for treating disease due to the various benefits they offer in the curing process. Several treatments using stem cells have undergone clinical trials, such as cell-based therapies for heart disease, sickle cell disease, thalassemia, etc. Adipose-derived stem cells are some of the many mesenchymal stem cells that exist in our body that can be harvested from the abdomen, thighs, etc. Adipose tissue is easy to harvest, and its stem cells can be obtained in higher volumes compared to stem cells harvested from bone marrow, for which a more invasive technique is required with a smaller volume obtained. Many scientists have expressed interest in investigating the role of adipose-derived stem cells in treating disease since their use was first described. This is due to these stem cells’ ability to differentiate into multiple lineages and secrete a variety of growth factors and proteins. Previous studies have found that the hormones, cytokines, and growth factors contained in adipose tissue play major roles in the metabolic regulation of adipose tissue, as well as in energy balance and whole-body homeostasis through their endocrine, autocrine, and paracrine functions. These are thought to be important contributors to the process of tissue repair and regeneration. However, it remains unclear how effective and safe ADSCs are in treating diseases. The research that has been carried out to date is in order to investigate the impact of ADSCs in disease treatment, as described in this review, to highlight its “trick or treat” effect in medical treatment.